Understanding their story: The role of work-life balance for African American males in the journey to senior leadership in community colleges - Sanford, Mark (My University, 2026)
Considering the expected leadership crisis in community colleges there should be an effort to develop a robust and diverse pipeline. African American males however remain underrepresented in senior executive roles. The purpose of this qualitative, narrative inquiry study was to explore the experience and perceptions of work-life balance for African American males in their journey to senior leadership in community colleges and to understand how social influences affected their work-life balance during this journey. This study guided by Work-Life Border Theory and Social Capital Theory, utilized a qualitative narrative inquiry methodology, using in-depth interviews conducted with 12 African American community college senior leaders, including Chancellors, Presidents and Provosts, Vice Chancellors/Provosts, Associate Vice Chancellors/Provosts and Campus Presidents with at least five years of senior level experience representing eight community colleges across four U.S. regions. Using Saldana’s (2021) coding methods, data were systematically analyzed incorporating In Vivo, Descriptive and Pattern coding to restory the participants journey and generate categories and themes. The analysis revealed five major themes. (1) The High Cost of Seeking Career Advancement, (2) Installing Boundaries is Critical to Achieving Work-Life Balance, (3) Overcoming Obstacles Along the Journey is Imperative to Success, (4) Leadership Development and External Networks, (5) The Burden of a Successful Journey Can be Daunting. Participants experienced significant work-life conflict as work and home life borders overlapped during their career ascent, making mad sacrifices that led to extreme fatigue. To survive these executives had to install strict boundaries, or guardrails to reclaim family and personal time. In addition, the climb was filled with invisible racism and institutional barriers that required immense psychological effort to overcome. Often blocked by hostile or rigid internal institutional borders, participants navigated their progression by relying heavily on external bridging capital such as AACC, Aspen Presidential Fellowship, Lakin Institute and bonding from capital from fraternities and HBCU and other mentors. This study concludes that for African American male leaders, traditional work-life balance is largely a myth, replaced by fierce strategic border management. These leaders ultimately experienced a unique cultural taxation,
Keywords: Work-life balance for African American males